An Advanced STATCOM Model for Optimal Power Flows Using Newton's Method - Kazemtabrizi, B; Acha, E (IEEE Transactions on Power Systems, 2014)
This paper presents the optimal power flow (OPF) formulation of a recent power flow STATCOM model. The new model puts forward an alternative, insightful interpretation of the fundamental frequency operation of the PWM-controlled voltage source converter (VSC), in an optimal fashion. The new model makes provisions for the explicit representation of the converter's internal ohmic and switching losses which in the context of an OPF formulation, yields an optimum operating point at which these power losses are at a minimum. The STATCOM model possesses unparalleled control capabilities in the operational parameters of both the AC and DC sides of the converter. Such control modeling flexibility is at its best when expressed in the context of an OPF solution using Newton's method. The STATCOM equations are incorporated into the OPF formulation using Lagrangian functions in quite a natural manner for efficient optimal solutions using a single frame-of-reference. The inequality constraint set of variables is handled equally well using the multipliers method. The prowess of the new model is demonstrated using two sample systems.
EPrint Processing Status: Full text deposited in DRO
Keywords: FACTS; Newton's method; STATCOM; Optimal power flows; Voltage source converter.